Monumental politics as a factor for forming historical memory policy and supporting ethnic self-identification (on the example of the North Caucasian peoples) - Svetlana Grigorievna Kudaeva (Вестник Майкопского государственного технологического университета, 2023)
The problem of the relationship between monumental politics and the politics of historical memory is increasingly attracting the attention of scientists and the public. This is due to the fact that conflict situations periodically arise associated with publicly formed historical memory in the form of monumental art. The article makes an attempt to comprehend the concepts of politics of memory, historical memory and their influence on the formation of monumental politics and culture of commemoration relying on the scientific concepts of M. Halbwachs, J. Assman and others and to consider monumental politics as an instrument of memory politics in the context of modern socio-political processes in the Caucasus, its role in the construction of national identity, maintaining historical memory and influencing interethnic relations. In the course of the research the author uses the method of retrospective analysis, since the formulation of the problem requires the reconstruction of the historical process, fixation of the available conclusions and their influence on the state of public opinion. The combination of retrospective and problem-chronological methods with the principles of historicism and objectivity has made it possible to consider events in an interconnected and unbiased manner.